PROGRAMA DE ASIGNACIÓN FAMILIAR DO PLAN DE EQUIDAD (AFAM-PE) DO URUGUAI: uma avaliação política da política. - CAMEJO CASAÑA, Maria Soledad (2018)
This thesis presents a policy evaluation of the program “Asignacion Familiar from the Plan de Equidad” (AFAM-PE) of Uruguay, so it is an evaluation that focuses on elucidating the political criterion and ideological guidelines with which was formulated this program. Made from the documentary analysis, the study looks first at the background preceding the program, from a historical review of policy “Asignación Familiar” , that has a long-standing in Uruguay. Made this, tackles to the historical context in which the AFAM-PE arises, especially based on a set of changes proposed by the progressive government in a social protection matrix of the country. Specifically the analysis is focused on understanding the meaning and content purchased by the proposal to modernize the network of assistance and social integration, within which took place the emergence of the “Ministerio de Desarrollo Social” (MIDES) and the plans of “Emergencia” (PANES) and “Equidad”. The latter plan is the framework within which emerges the AFAM-PE program as a Rental Income Transfer Program (PTRC), in which was placed a singular importance as tool for attending the situations of "socio economic vulnerability." For other part, the study also discusses the key components that structure this particular program, with special emphasis on three element analysis, which are the criteria that guide the amount transferred, the emphasis on the conditionality and criteria for defining access to program. From this analysis can reflect that this particular program, although it has been placed as the manifestation of a government act that propo sed meet a priority the most disadvantaged sectors of the population, its structure has acquired a number of components and limitation that reflect neoliberal ideas of guilt and individual responsibility. In summary it can be concluded that in addition to social rights expansion rhetoric surrounding the program and own “Plan de Equidad”, appear contradictory elements. In this sense, the policy option for expanding the social assistance in response to the impoverishment processes took place within a strategy in which the tendency is understand social policy out or even in opposition to economic relations without putting the forms of creation and accumulation wealth as a problem to intervene.